Isolation of Antibiotic Resistant Bacteria from Healthy Individuals in Nilai, Negeri Sembilan. - Lim, Eric Chuah Han; Ambigai, Lalita; Subramaniam, Geetha (2016)
The emergence of antibiotic resistant bacteria is a major problem worldwide. Some of the common cause for the spread of antibiotic resistant bacteria include the improper use of antibiotics and poor hygiene practices. Healthy individuals can be carriers of antibiotic resistant bacteria. One of such antibiotic resistant bacteria is the methicillin resistant S. aureus (MRSA), a common skin microflora. These individuals can transmit antibiotic resistant bacteria to others causing outbreaks of diseases. Thus, the aim of this study was to isolate antibiotic resistant bacteria from the nasal cavity and axilla of 28 healthy individuals in Nilai, Negeri Sembilan. The pure culture of the respective isolates were grown on Mannitol Salt Agar (MSA) and subjected to catalase test for identification. Antibiotic susceptibility testing was then conducted to determine the susceptibility of bacteria towards the tested antibiotics using the disc diffusion method. Out of the 40 isolates, 36 isolates showed resistance based on the BSAC guidelines, version 6.0, 2016.The bacteria that were Gram-positive cocci with clusterlike cell arrangement, catalase positive, and resistant to oxacillin were subjected to inoculation onto Brilliance MRSA 2 agar. Twenty-four MRSA were isolated while 12 MRSE might have been isolated. Although further studies are required, this preliminary finding can be used to create an awareness among the public to prevent the spread of antibiotic resistant bacteria